Penyuluhan Aplikasi ms. Powerpoint Bagi Guru Brainfor Islamic School Kisaran Timur - Suparmadi Suparmadi; Mhd Ihsan; Akmal Akmal (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
Abstract: School Brainfor Islamic School is in the town of Kisaran, Asahan District, a school that has only a few classes. However, teaching process activities are minimal and require variations and methods used with material explanation techniques using book media as well as whiteboards and demonstration tools. With the development of the method of using Ms. PowerPoint aims to be able to help teachers or schools in the use of delivering varied material both in class for presenting material to students and for presentations between school parties to parents of students. This dedication aims at none other than to provide education to the school, and counseling so that they are able to use the Ms. application. Powerpoint. With this activity, counseling also uses socialization, discussion, and training methods as well as assistance to partners so they can operate the Ms. application. Powerpoint. The result to be achieved in this service is that more partners will be able to use familiar application methods or media. Paying attention to supporting the process of delivering teaching material using Ms. Powerpoint to add insight and be able to take advantage of digital media.Keywords: IT; Material; Ms. Powerpoint Abstrak: Sekolah Brainfor Islamic School berada di kota Kisaran, Kabupaten Asahan, sekolah yang memiliki hanya beberapa kelas. Akan tetapi Kegiatan proses mengajar yang minim dan  membutuhkan  variasi serta metode yang menggunakan dengan teknik penjelasan materi menggunakan media buku maupun papan tulis dan alat praga. Dengan adanya perkembangan metode penggunaan aplikasi Ms. powerpoint bertujuan agar dapat membantu bagi guru atau pihak sekolah dalam kegunaan penyampaian materi yang bervariatif baik saat di dalam kelas untuk pemaparan materi ke peserta didik maupun pemaparan rapat antar pihak sekolah ke wali murid. Pengabdian ini bertujuan tidak lain dan tidak bukan untuk memberikan edukasi kepada pihak sekolah, penyuluhan agar mampu menggunakan aplikasi Ms. Powerpoint. Dengan kegiatan ini pula penyuluhan menggunakan metode sosialisasi, diskusi dan pelatihan serta pendampingan kepada mitra agar dapat mengoperasikan aplikasi Ms. Powerpoint. Hasil yang akan dicapai dalam pengabdian ini adalah akan bertambahnya mitra dapat menggunakan metode atau media aplikasi tidak asing lagi. Memperhatikan dalam penunjang proses penyampaian materi pengajaran menggunakan aplikasi Ms. Powerpoint untuk menambah wawasan dan dapat memanfaatkan media digital.Kata Kunci: IT; Materi; Ms. Powerpoint